BUILDING ECOLOGICAL AWARENESS BASED ON LOCAL WISDOM: A STUDY OF MUSLIM FAMILIES OF THE TENGGER TRIBE IN CULTIVATING MULTICULTURAL VALUES - Yusuf, Achmad; Nurdin, Kurniawan Dindasari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The family is the 'vehicle' that shapes the character of its members. How families treat their children will impact their children's behavioural development. One type of education that parents can receive is environmental education, either through sacred, mysticism, or religion, packaged in certain cultures. This study aims to know, analyse, describe, and interpret multicultural education in Tengger Muslim families with insight into environmental conservation based on local culture in Mororejo Village, Tosari Regency.This study used qualitative phenomenology methods and data collection techniques with three techniques: interviews, observation and documentation. As for environmental management related to environmental conservation, the Tengger people pass it on to future generations or their children while they, together with their children, go to gardens and farms or forests to graze or look for firewood when the child is not in formal or informal school. There are various cultural rules in it, such as land or forests around Pedanyangan that cannot be used for agriculture and many forests that cannot be used for farming, which, of course, is told by parents to the children of the Tengger tribe. This applies to all, regardless of the parent's religious background. The concept of prohibition and management that leads to environmental preservation can be seen in traditional transcendental ceremonies, such as asking for safety through salvation, carried out by Muslim communities such as Wiwitan Bersih Desa and Leliwet.